Perinatal outcome of fetuses with congenital high airway obstruction syndrome: a single-center experience - Jeong, Sang-Hee; Lee, Mi-Young; Kang, Ok-Ju; Kim, Rina; Chung, Jin-Hoon; Won, Hye-Sung; Lee, Pil-Ryang; Jung, Euiseok; Lee, Byong Sop; Choi, Woo-Jong; Lee, Yoon Se (Obstetrics & gynecology science, 2021)
To report our experience with management of fetuses with congenital high airway obstruction syndrome (CHAOS). We retrospectively reviewed the cases of fetuses who were prenatally diagnosed and postnatally confirmed with CHAOS between 2010 and 2019 at Asan Medical Center, Seoul, Korea. Of 13 fetuses prenatally diagnosed with CHAOS, 7 were lost to follow-up and 6 were postnatally confirmed as having CHAOS. All fetuses, except one were delivered via cesarean section with an ex utero intrapartum treatment (EXIT) procedure. Two patients had coexisting congenital heart diseases requiring several cardiac surgeries following birth. Both of these patients demonstrated developmental delay; however, the remaining 4 had a normal development except for expressive language. Two infants died of respiratory complications, and the remaining 4 were alive at the end of the follow-up period. All 4 live patients underwent tracheostomy with planned reconstruction surgery. Three children are now able to phonate, and 1 can maintain a conservation. The proper management of CHAOS using the EXIT procedure results in high survival and low hypoxemia-induced complication rates. Therefore, an accurate prenatal diagnosis is necessary for an appropriate perinatal management.